Social context of child survival strategies among mothers in polygynous marriages in Ibadan, Nigeria (2018)
The study examined the social context of child survival strategies among mothers in polygynous marriages in Ibadan, Nigeria. The social exchange theory was employed as the theoretical framework. Thirty in-depth interviews were conducted with mothers in Polygynous marriages. Referral and snowball techniques were used to reach the target population. Mothers in polygynous marriages were purposively selected from three geographical locations in Ibadan, Nigeria. Manual content analysis was used to analyze the data for the study. The result showed that most mothers in polygynous marriages in Ibadan engaged in informal economic activities in order to raise finance needed for sustenance and child survival; use traditional herbs for child care, treatment and survival; live separately from other wives in order to prevent childhood sicknesses associated with congestion and overcrowding in the house. In addition, there is inconsistency in administering immunization to children due to poverty. The study concluded that mother’s place of residence, health care practices, and engaging in informal economic activities positively influenced child survival among women in polygynous marriages in Ibadan. There is need for more awareness campaign to ensure that children in polygynous families are regularly administered with vaccines in order to ensure their survival and achievement of the Sustainable Development Goal 3